ANALYSIS OF COPING MECHANISMS AND QUALITY OF LIFE IN MENOPAUSE WOMEN IN KAYE LEE VILLAGE, INGIN JAYA DISTRICT, ACEH BESAR DISTRICT - Ferdi Riansyah; Eridha Putra; Mardhatillah; Fitri Yanti; Mutia Abdullah; Desikaliana Desikaliana; fajriansyah fajriansyah; zubir zubir (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Menopause is the cessation of menstruation forever. Menopause usually occurs in women from the age of 45-55 years. The formulation of the problem in this study is Is There a Relationship Between Coping Mechanisms and Quality of Life in Menopausal Women in Kaye Lee Village, Wanna Jaya District, Aceh Besar District? The research design used was descriptive analytic with female research subjects who were categorized as menopausal in Kaye Lee Village, Want Jaya District, Aceh Besar District. The sampling technique used accidental sampling based on chance with a total of 55 people. The results of this study indicate a significant p-value (0.056 <0.05). Based on the results of the research above, it can be concluded that there is a significant relationship between coping mechanisms and quality of life in postmenopausal women in Kaye Lee Village, Wanna Jaya District, and Aceh Besar District. The coping mechanism or the way menopausal women manage their lives greatly affects their quality of life because women who enter menopause will experience various complaints caused by significant hormonal changes. There needs to be a good coping mechanism in postmenopausal women for emotional, physical, individual social well-being, as well as activities in daily life.